Fabrication of Energetic Composites with 91% Solid Content by 3D Direct Writing - Yucheng Deng; Xinzhou Wu; Peng Deng; Fayang Guan; Hui Ren (Micromachines, 2021)
Direct writing is a rapidly developing manufacturing technology that is convenient, adaptable and automated. It has been used in energetic composites to manufacture complex structures, improve product safety, and reduce waste. This work is aimed at probing the formability properties and combustion performances of aluminum/ammonium perchlorate with a high solid content for direct writing fabrication. Four kinds of samples with different solid content were successfully printed by adjusting printing parameters and inks formulas with excellent rheological behavior and combustion properties. A high solid content of 91% was manufactured and facile processed into complex structures. Micromorphology, rheology, density, burning rate, heat of combustion and combustion performance were evaluated to characterized four kinds of samples. As the solid content increases, the density, burning rate and heat of combustion are greatly enhanced. Based on 3D direct writing technology, complex energetic 3D structures with 91% solid content are shaped easier and more flexibly than in traditional manufacturing process, which provides a novel way for the manufacture of complicated structures of energetic components.